2020
DOI: 10.3389/fonc.2020.01540
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiotherapy in Combination With Chemotherapy Improves Outcome of Patients With Esophageal Carcinoma Tracheoesophageal Groove Lymph Node Metastasis

Abstract: This study investigated the efficiency and safety of hypofractionated radiotherapy (HFR) combined with paclitaxel chemotherapy for the treatment of postsurgery tracheoesophageal groove lymph node (TGLN) metastasis in patients with esophageal cancer (EC). Fifty-three EC patients with TGLN metastasis after surgery admitted to the Yancheng Third People’s Hospital from January 2013 to June 2015 were included in this study. They were randomly divided into the HFR group ( n = 25) and conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There are studies demonstrating a survival benefit of this approach particularly in the context of metastatic nodal disease. In one such study, hypofractionated radiotherapy (HFR) administered with taxane based chemotherapy in the management of post-surgery tracheoesophageal groove lymph node (TGLN) metastasis demonstrated improved OS in the HFR group compared with that of the conventional dosing treatment arm [24.1 mo (95%CI, 16.2-32.1 mo) vs 11.9 mo (95%CI, 9.2-14.4 mo), P = 0.024)[ 28 ]. Importantly, the study did not find a significant difference in pulmonary complications such as radiation pneumonitis (grades 3-4, 16.0% vs 7.1%; P = 0.314)[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies demonstrating a survival benefit of this approach particularly in the context of metastatic nodal disease. In one such study, hypofractionated radiotherapy (HFR) administered with taxane based chemotherapy in the management of post-surgery tracheoesophageal groove lymph node (TGLN) metastasis demonstrated improved OS in the HFR group compared with that of the conventional dosing treatment arm [24.1 mo (95%CI, 16.2-32.1 mo) vs 11.9 mo (95%CI, 9.2-14.4 mo), P = 0.024)[ 28 ]. Importantly, the study did not find a significant difference in pulmonary complications such as radiation pneumonitis (grades 3-4, 16.0% vs 7.1%; P = 0.314)[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency and safety of hypofractionated radiotherapy (HFR) combined with paclitaxel chemotherapy for the treatment of post surgery tracheoesophageal groove lymph node (TGLN) metastasis in patients with esophageal cancer were investigated by Jian Wang et al ( Wang et al, 2020 ). They found that the combination of hypofractionated radiotherapy (HFR) and chemotherapy improved the prognosis of esophageal cancer patients with tracheoesophageal groove lymph node (TGLN) metastasis with no increased adverse events.…”
mentioning
confidence: 99%